Fitofarmacología de Tamarindus indica - Akram, Muhammad (2022)
Tamarindus indica is a well-known medicinal plant which belongs to Fabaceae family, and it is a tropical perennial plant, which is broadly consumed as conventional system of pharmaceutical in whole world. T. indica is generally cultivated in Africa and Southern Asian zones. This review precis the Phytochemistry as well as pharmacological properties of T. indica. The chemistry of this plant detailed have place to various classes such as tannins, glycosides, flavonoids, steroids, unstable oils, tars, sugars, and mucilage. T. indica has various therapeutically properties, numerous of which have been confirmed by logical researchers. Phytochemical composition of T. indica confers it important pharmacological properties at present to recommend its habitual consumption to chronics disseases.